Maternal and child health care access to skilled delivery services among Ghanaian rural mothers - Adongo, Awinaba Amoah; Dapaah, Jonathan Mensah; Azumah, Francess Dufie; Onzaberigu, John Nachinaab (Research in Health Services & Regions, 2024)
Introduction Most new-born babies are born at home in rural communities which is not new phenomenon due to lack of access to primary healthcare services and trained skilled health attendants, exposing mothers and children to a high risk of labour complications. The purpose of this study was to better understand factors influence rural women's access to primary health care and skilled delivery services as well as their reasons for using or not using maternal health care and skilled delivery services. Methods The study employed a social survey design with a quantitative approach to data analysis. Cluster Sampling was used, possibly based on rural communities, to efficiently collect data from different geographic locations. Simple random sampling individuals from each cluster ensures that all eligible individuals have an equal chance of being included in the study. This enhances the representativity of the sample. A total of 366 mothers were selected from four rural communities in the North East Region of Ghana. The choice of sample size considered factors like the study's objectives, available resources, and the desired level of statistical power. Data was primarily gathered through the administration of a questionnaire to the respondents. Factors considered for achieving representativity include, geographic representation, accessibility, healthcare infrastructure and healthcare professionals’ attitudes . Findings The study found that distance to health centres limits women's access to skilled delivery services. Lack of primary health facilities in the rural communities hamper maternal and child care services delivery. The attitude of health care professionals determines a mother’s utilisation of maternal health care and skilled delivery services. Conclusion The study contributes to the limited research on maternal health services and their impact on mother and child health in the study area. This study is one of the first to investigate into maternal health care as a key predictor of mother and child health in the study area. The study's theoretical lens was the Andersen and Newman Health Behavioural Model theory, which supports the explanation of distance, lack of primary health centres, attitudes and lack of skilled personnel to the non-utilisation of maternal and health services in rural communities. The study recommended that primary healthcare facilities and trained health professionals should be a priority of government in rural communities to promote maternal and child healthcare.